2014
DOI: 10.1371/journal.pone.0102354
|View full text |Cite
|
Sign up to set email alerts
|

The Submarine Volcano Eruption off El Hierro Island: Effects on the Scattering Migrant Biota and the Evolution of the Pelagic Communities

Abstract: The submarine volcano eruption off El Hierro Island (Canary Islands) on 10 October 2011 promoted dramatic perturbation of the water column leading to changes in the distribution of pelagic fauna. To study the response of the scattering biota, we combined acoustic data with hydrographic profiles and concurrent sea surface turbidity indexes from satellite imagery. We also monitored changes in the plankton and nekton communities through the eruptive and post-eruptive phases. Decrease of oxygen, acidification, ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
(54 reference statements)
1
18
1
1
Order By: Relevance
“…This fraction and other large migrant species were collected using the MOHT, a sampling device that has proved to be highly effective at capturing krill and juvenile fish (Oozeki et al, 2004;Yamamura et al, 2010). In fact, our results showed that these small organisms are an important component of migrant micronekton, which has been systematically biased in previous studies using large commercial trawls (see Wienerroither et al, 2009;Bordes et al, 2009;Ariza et al, 2014;Landeira et al, 2012). However, these studies also revealed that the MOHT sampled the adult fraction of several myctophid species and other large migrating fish poorly (e.g., Gonostoma or Chauliodus).…”
Section: Methodological Approaches and Constraintscontrasting
confidence: 56%
“…This fraction and other large migrant species were collected using the MOHT, a sampling device that has proved to be highly effective at capturing krill and juvenile fish (Oozeki et al, 2004;Yamamura et al, 2010). In fact, our results showed that these small organisms are an important component of migrant micronekton, which has been systematically biased in previous studies using large commercial trawls (see Wienerroither et al, 2009;Bordes et al, 2009;Ariza et al, 2014;Landeira et al, 2012). However, these studies also revealed that the MOHT sampled the adult fraction of several myctophid species and other large migrating fish poorly (e.g., Gonostoma or Chauliodus).…”
Section: Methodological Approaches and Constraintscontrasting
confidence: 56%
“…There are natural analogs to the different forms of tailings disturbance described above. For example natural massive sedimentation can result from volcanic eruptions (Ariza et al, 2014), slumps, slides, debris flows and turbidity flows on margins (Masson, 1996), iceberg scouring, tectonically induced mass wasting or storm induced flows of slope or canyon sediments, flood deposits from land and benthic storms that suspend and redeposit seafloor sediments (Aller, 1989;Wheatcroft, 2000). Volcanic eruptions can deposit massive ash layers on the seafloor (Cita and Podenzani, 1980;Hess and Kuhnt, 1996).…”
Section: Parallels With Other Forms Of Disturbancementioning
confidence: 99%
“…These physical-chemical anomalies had strong effects on some pelagic communities. Dead fish were observed floating on surface waters, no fish schools were acoustically detected within the affected area [ 12 ] and the diel vertical migration of zooplankton was disrupted [ 14 ]. Furthermore, preliminary results reported that the activity of the local microbial communities was also significantly altered.…”
Section: Introductionmentioning
confidence: 99%